2017
DOI: 10.1007/s11010-017-3156-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation of ATF4 and GADD34 in Neuro2a cells by CRISPR/Cas9-mediated genome editing

Abstract: Activating transcription factor 4 (ATF4), which is ubiquitously expressed, plays a crucial role in regulating various stress-responsive genes under pathophysiological conditions. Further, growth arrest and DNA damage-inducible gene 34 (GADD34), a downstream target of ATF4, has been reported to negatively regulate ATF4 expression. To understand the relationship between intrinsic ATF4 and GADD34 under resting and ER stress conditions, we used a novel gene editing approach, CRISPR/Cas9, to integrate antibiotic-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Among the tissues we tested, CRELD2 expression in brain was not so high. On the other hand, we first identified CRELD2 as a novel ER stress-inducible gene using microarray analysis of Tg-treated mouse neuroblastoma cell-line, Neuro2a 3 , and have been employing this Neuro2a cells to elucidate several ER stress gene expression (e.g., MANF, Chac1 and GADD153) in detail 17 , 19 , 20 . On the basis of our previous findings, we next investigated the expression of CRELD2 mRNA and protein in Neuro2a cells after treatment with three well-used ER stress-inducing stimuli (Tg, Tm and BFA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the tissues we tested, CRELD2 expression in brain was not so high. On the other hand, we first identified CRELD2 as a novel ER stress-inducible gene using microarray analysis of Tg-treated mouse neuroblastoma cell-line, Neuro2a 3 , and have been employing this Neuro2a cells to elucidate several ER stress gene expression (e.g., MANF, Chac1 and GADD153) in detail 17 , 19 , 20 . On the basis of our previous findings, we next investigated the expression of CRELD2 mRNA and protein in Neuro2a cells after treatment with three well-used ER stress-inducing stimuli (Tg, Tm and BFA).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we first investigated the expression of intrinsic CRELD2 in mouse tissues and Neuro2a cells after treatment with several reagents. Furthermore, we established the CRELD2-deficient Neuro2a cells using a CRISPR/Cas9 system 16 , 17 and characterized the molecular features of this protein. Especially, we showed that CRELD2 was not directly associated with typical ER stress-inducible factor expression in response to tunicamycin (Tm), but its depletion rendered the cells vulnerable to Tm stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of SEL1L-and homocysteine-induced ER protein (Herp)-deficient HEK293 cells was performed using the clustered regularly interspaced short palindromic repeats/CRISPR-associated proteins 9 (Cas9) system as described previously [10,11]. As shown in Fig.…”
Section: Establishment Of Sel1l-and Herp-deficient Hek293 Cellsmentioning
confidence: 99%
“…To estimate the expression level of each gene by RT-PCR, total RNA was extracted from cells lysed with TRIzol and converted to cDNA by reverse transcription using random ninemers with Prime SuperScript III RT (Life Technologies, Waltham, MA, USA), as previously described [10]. Each cDNA sample was added to a PCR mixture for amplification (NEB, Ipswich, MA, USA).…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
See 1 more Smart Citation